2003
DOI: 10.5144/0256-4947.2003.249
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Dysphagia

Abstract: AM Al-Shehri, Drug-Induced Dysphagia. 2003; 23(5): 249-253 Dysphagia is related to the impairment of food passage from the mouth to the stomach. It describes disability or problems in swallowing a wet or dry bolus properly. Dysphagia can be accompanied by a pain sensation in the chest, mostly caused by impaction of the food bolus in the esophagus. Dysphagia should not be confused with the globus sensation (globus hystericus), a feeling of having a lump in the throat, which is unrelated to swallowing and occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Difficulty with swallowing medications has been reported in 15-30% of aged care residents [4,5]. This can be a result of agerelated physiological changes in their swallowing function, a sequela of different co-morbidities, or a side effect of polypharmacy [1,[6][7][8]. In addition to swallowing difficulties, other factors such as psychological aversion to taking medications or declined cognitive function may compromise older patients' ability to swallow medications safely [9].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty with swallowing medications has been reported in 15-30% of aged care residents [4,5]. This can be a result of agerelated physiological changes in their swallowing function, a sequela of different co-morbidities, or a side effect of polypharmacy [1,[6][7][8]. In addition to swallowing difficulties, other factors such as psychological aversion to taking medications or declined cognitive function may compromise older patients' ability to swallow medications safely [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear need for studies evaluating the effectiveness of dysphagia interventions in this group using randomized controlled trials. (''ECT'') of (MH ''Electroconvulsive Therapy'') S24 S1 or S2 or S3 or S4 or S5 S25 S5 or S6 or S7 or S8 or S9 or S10 or S11 or S12 or S13 or S14 or S15 or S16 or S17 or S18 or S19 or S20 or S21 or S22 S26 S24 and S25 [4] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [5] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [27] Review article [28] Commentary [29] Letter to the editor with case report [30] Study not related to dysphagia [31] Duplicate data presented in [31] which was included in the review [32] Review of another author's work. Not original article [33] Case report [34] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [35] Commentary [36] Letter to the editor [37] Letter to the editor [38] Outcomes for general population (not limited to population of interest) [39] Case report [40] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [41] Review article [42] Abstract from conference proceedings [43] Unable to locate article [44] Outcomes for general population (not limited to population of interest) [45] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [46] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [47] Letter to the editor [48] Single-case studies [49] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [50] Letter to the editor [51] Letter to the editor with single-case report [52] Commentary [53] Letter to the editor [54] Medication guideline.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to these patients, many other patients had taken drugs that can cause xerostomia, drowsiness, and confusion. In earlier studies, these drugs are reported to possibly induce dysphagia [ 16 ], and the above-mentioned symptoms are likely to affect swallowing. However, these patients were included in the unknown group because of the relatively low correlation of these drugs with dysphagia.…”
Section: Discussionmentioning
confidence: 99%